DNR1 Regulates apoptosis: new insights into mosquito apoptosis - Devore, Casey Leigh (Kansas State University, 2011)
Apoptosis, or programmed cell death, is a crucial conserved process among organisms for deleting damaged unwanted cells, as well as for development and viral defense, and plays an important role in multiple diseases. Too much apoptosis may lead to Alzheimer’s disease, and too little may result in cancer. Therefore, the ability to understand this process is essential for improved medical knowledge today. Apoptosis has been explored in a number of species and pathways seem relatively conserved among most, with unique aspects contained in each, but little is known about apoptosis in mosquitoes. Improved knowledge and growing interest concerning apoptosis in mosquitoes is necessary considering the vast health effects seen across the globe as a result of diseases transferred by the mosquito vector. The Dengue virus mosquito vector Aedes aegypti was the focus here. A new player named defense repressor 1 was discovered in Drosophila melanogaster (DmDnr1), shown to play a role in apoptosis, and the homolog discovered in A. aegypti (AeDnr1). Silencing Dmdnr1 resulted in cells sensitized to apoptosis but was not enough to induce spontaneous apoptosis. In contrast, silencing Aednr1 in the A. aegypti cell line, Aag2, led to spontaneously induced apoptosis. This showed the importance of AeDnr1 as a member of the apoptotic pathway in this species. Epistasis experiments showed that apoptosis induced by silencing Aednr1 requires the initiator caspase Dronc and the effector caspase CASPS8, whereas apoptosis induced by silencing the inhibitor of apoptosis, Aeiap1, also requires Dronc but acts through the effector caspase CASPS7. Further epistasis experiments showed that apoptosis induced by silencing Aednr1 requires the IAP antagonist Mx, but not IMP. This showed for the first time a gene regulating upstream of an IAP antagonist. Biochemical studies showed that AeDnr1 regulates active CASPS8 but not CASPS7, and interacts with Mx and CASPS8 but not AeDronc, CASPS7 nor AeIAP1. Studies also showed Mx competes effectively with CASPS8 but not CASPS7 for AeIAP1 binding, and IMP competes effectively with CASPS7 but not CASPS8 for AeIAP1 binding. An improved apoptosis pathway for the mosquito A. aegypti emerged involving a potential feedback loop with explanations for the upstream IAP antagonist preference as well as the downstream effector caspase preference resulting from apoptosis induced by Aednr1 silencing. Through the discussed research, multiple unique findings resulted. Studying the mosquito model will allow us to find certain gene relations that are more difficult to uncover in the Drosophila model. Because Dnr1 is found in most systems, this improved pathway may shed light not only on a potential role of Dnr1 in apoptosis in insects but higher organisms as well.
Keywords: Apoptosis; Vector biology; Mosquitoes; Medical entomology; Biochemistry (0487); Cellular Biology (0379); Entomology (0353)